Evaluation of cognition enhancing activity of pioglitazone in albino mice - L., Shruthi S.; L., Kalabharathi H.; Amoghimath, Siddamma (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Worldwide, 47.5 million people have dementia, with just over half (58%) living in low- and middle-income countries. Every year, there are 7.7 million new cases. The estimated proportion of the general population aged 60 and over with dementia at a given time is between 5 to 8 per 100 people. The total number of people with dementia is projected to be 75.6 million in 2030 and almost triple by 2050 to 135.5 million. Methods: All animals were allowed to acclimatize with laboratory conditions at least two weeks before starting the experiment and they were maintained under the same condition throughout the experiment. They were given food and water ad libitum. The experiments were performed as per the Committee for the Purpose of Control and Supervision on Experiments on Animals (CPCSEA) guidelines. The animals were subjected to experimentation between 0900-1600 hours in noise free atmosphere with ambient temperature 23-300ºC. Results: The Pioglitazone treated groups showed statistically significant results in the SDL when compared to the control group (p<0.01 on both days) and the scopolamine group (p<0.01 on both days) on both acquisition day and retention day. Conclusions: There was no significant difference in SDL in standard and Pioglitazone treated groups on both acquisition day and retention day.